2011
DOI: 10.1038/leu.2011.103
|View full text |Cite
|
Sign up to set email alerts
|

p53 and Notch signaling in chronic lymphocytic leukemia: clues to identifying novel therapeutic strategies

Abstract: The p53 tumor suppressor protein has a key role in the induction of apoptosis of chronic lymphocytic leukemia (CLL) cells. Abnormalities within the p53 pathway identify a subset of patients with a poor prognosis. This review describes recent advances in understanding the mechanisms that regulate p53 levels and the role of p53 in the control of the cell cycle and of apoptosis. The classical model of p53-mediated apoptosis emphasizes the transcriptional activation of proapoptotic genes. In contrast, a novel mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 81 publications
1
40
0
Order By: Relevance
“…A number of developmental signaling pathways, including Notch, PI3K/Akt, Wnt/β-catenin, Hedgehog and p53, [49][50][51] have been shown to have central roles in mammary tumorigenesis and stem cell biology. Activation of the PI3K/ Akt pathway has emerged as a central feature of EMT.…”
Section: Figure 4 Continuedmentioning
confidence: 99%
“…A number of developmental signaling pathways, including Notch, PI3K/Akt, Wnt/β-catenin, Hedgehog and p53, [49][50][51] have been shown to have central roles in mammary tumorigenesis and stem cell biology. Activation of the PI3K/ Akt pathway has emerged as a central feature of EMT.…”
Section: Figure 4 Continuedmentioning
confidence: 99%
“…33 For this, DNA was extracted according to standard methods from bone marrow and peripheral blood cells obtained at the time of diagnosis. Next-generation amplicon deep-sequencing (Illumina, San Diego, CA; 454 Life Sciences, Branford, CT) was applied to investigate the mutational hotspot regions of TP53 34 (ENST00000269305, exons [4][5][6][7][8][9][10][11]. next generation sequencing data were analyzed using the GS Amplicon Variant Analyzer Software 2.6 (454 Life Sciences) and Sequence Pilot (version 4.1.1 Build 514 for the 454 platform; version 4.1.1 Build 510 for the Illumina platform, JSI Medicalsystems, Kippenheim, Germany).…”
Section: Mutation Analysismentioning
confidence: 99%
“…However, the frequency and prognostic impact of TP53 mutations has only rarely been studied in ALL thus far. Mutations in or deletion of TP53 are generally associated with advanced stages of disease, 7 insufficient response to therapy, 8,9 and a poor prognosis. 10,11 TP53 is a transcription factor and functions as key tumor suppressor and master regulator of various signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] We and others have recently demonstrated that higher expression of angiopoietin-2 (ANGPT2) in CLL confers poor prognosis and that the ANGPT2 produced by leukemic cells is able to induce an increased angiogenesis, characteristic of CLL patients with an aggressive disease. [5][6][7][8][9][10] ANGPT2 is a secreted glycoprotein able to increase vessel plasticity, by binding to the Tie-2 receptor on endothelial cells and blocking ANGPT1 function.…”
Section: Introductionmentioning
confidence: 99%